Decreased serum levels of TGF-β in patients with acute Plasmodium falciparum malaria - C. Wenisch (2018)
Apart from cellular immunity and immunopathology, various cytokines have been implicated in malaria-associated immunosuppression. In this study, serum levels of transforming growth factor-β (TGF-β) were determined with an enzyme-linked immunosorbent assay in 37 patients with acute Plasmodium falciparum malaria prior to, during, and after therapy and in 17 healthy controls in Bangkok, Thailand. Patients were treated with artesunate and mefloquine. TGF-β serum levels were found decreased prior to treatment (14±11 pg/ml versus 63±15 pg/ml in healthy controls;P<0.05). The serum concentrations of TGF-β increased after initiation of treatment and were within normal range on day 21. Serum levels of both tumor necrosis factor-ga (TNF-α) and soluble TNF-receptor 55 kDa were inversely correlated to serum levels of TGF-β (r= -0.667 and r=}-0.592, n=37; respectively, P < 0.05 for both). No correlation between parasitemia and serum levels of TGF-β could be found. The results are compatible with a decreased production and release, an enhanced clearance or utilization, or tissue accumulation of TGF-β in acute P. falciparum malaria. © 1995 Plenum Publishing Corporation.